Employee Welfare Measures with Special Reference to National Thermal Power Corporation - Narender, S; Abbaraboina, Gopikrishna (Journal of Commerce and Trade, 2015)
To know that whether welfare facilities play an important role on the working of employees, And to know hence the employees are dissatisfied welfare facilities will help them to get motivated. Employees play an important role in the industrial production of the country. Hence, organizations have to secure the cooperation of employees in order to increase the production and to earn higher profits. The cooperation of employees is possible only when they are fully satisfied with their employer and the working conditions on the job. In the past, industrialists and the employers believed that their only duty towards their employees was to pay them satisfactory wages and salaries. Therefore, this study focuses on employee welfare measures in NTPC, Ramagundam.